Perilaku tegangan-regangan beton yang terbuat dari agregat ringan buatan yang diperkuat dengan carbon fiber reinforced polymer - Louk Fanggi, Butje Alfonsius; Suswanto, Budi; Tajunnisa, Yuyun; Basshofi Habieb, Ahmad; Meynerd Rafael, Jusuf Wilson; Habibillah Asyari, Yudhistira; Rijiyawanto, Adetya; Syifaul Ummah, Galih (JURNAL TEKNIK SIPIL, 2023)
This paper describes the findings of a research study aimed at evaluating the impact of various parameters on the stress-strain behavior of concrete composed of artificial lightweight aggregates with rectangular cross-sections. The factors that were evaluated include the number of fiber-reinforced polymer (FRP) layers, the compressive strength of the concrete, and the cross-sectional shape of the concrete. A total of twenty-two test specimens were fabricated, wrapped with Fiber Reinforced Polymer (FRP), and subjected to concentric compressive loading for experimental evaluation. The experimental findings indicate that Fiber Reinforced Polymer (FRP) demonstrates an excellent wrapping technique for lightweight concrete composed of lightweight aggregate. In addition to this, the test findings indicate a positive correlation between the number of fiber-reinforced polymer (FRP) layers employed and the resultant ultimate stress and strain shown by concrete composed of artificial lightweight aggregate. The test results additionally demonstrate a clear relationship between the rise in ultimate stress and the compressive strength of concrete, while showing an inverse relationship with the ultimate strain observed. Similarly, the test results indicate that the utilization of Fiber Reinforced Polymer (FRP) wrapping has more efficacy when applied to round cross-sectional shapes as opposed to rectangular cross-sectional shapes.